Takmil wal istikmal complementarity in sustaining community support agriculture for vegetable farming in Malaysia - Mhd. Sarif, Suhaimi; Ismail, Yusof (2019)
Community support agriculture enables community to collaborate, cooperate and complement among for vegetable farming. The community support agriculture has been practiced among traditional farmers of vegetables and fruits. Takmil wal istikmal among farmers and community on complementarity basis is linking them to takmil wal istikmal in sustaining responsible consumption and production. Mass vegetable and fruits farming with modern farming approach contributes to unhealthy vegetable and fruit consumption. When vegetable farmers and non farmers are working on common objective that is to have fresh and organic vegetables and fruits, they will cooperate, complement and consolidate relationships. This study explores takmil wal istikmal complementarity in sustaining community support agriculture (CSA) with farmers and stakeholders. The study employs personal interview with selected farmers, administrators of community support agriculture and regulators of agriculture in Malaysia. The interview results show that there is limited takmil wal istikmal.